Tanggung Jawab Notaris Atas Akta Perjanjian Pengikatan Jual Beli Saham Yang Dibalut Dengan Hutang Piutang - Samsidar; Putra Hutomo; Mulyadi; Samsidar Samsidar; Mulyadi Mulyadi (Bajang Institute, 2026)
Stock sale and purchase transactions are not always conducted directly; rather, they are often preceded by a Share Sale and Purchase Binding Agreement (PPJB), which in practice may take the form of a share sale deed intertwined with a debt arrangement. Such agreements constitute a complex legal instrument because they combine two distinct legal aspects sale and purchase and loan agreements thereby giving rise to particular legal implications. The research addresses two main issues: (1) the legal consequences of a share sale and purchase binding agreement that is intertwined with a debt arrangement, and (2) the liability of notaries in the drafting of such agreements. This study employs a normative juridical method, namely library-based legal research that relies on secondary data derived from primary, secondary, and tertiary legal materials. The research adopts statutory and conceptual approaches, while the collection of legal materials is carried out through the identification and inventory of positive legal rules, literature, books, journals, and other legal sources. The analysis of legal materials is conducted through systematic and grammatical legal interpretation, as well as the application of legal construction methods. The results indicate that the use of a share PPJB as an instrument for debt arrangements has the potential to create legal uncertainty, particularly with regard to proving the parties’ intent and the mechanism for executing share collateral. Furthermore, notaries play a central role both formally and substantively; therefore, where a deed results in losses due to a lack of due diligence, the notary may be held liable both civilly and under professional ethics